Sprint and vertical jump performances are not affected by six weeks of static hamstring stretching - Bazett-Jones, D. M.; Gibson, M. H.; McBride, J. M. (The Journal of Strength and Conditioning Research, 2008)
The purpose of this study was to investigate whether 6 weeks of static hamstring stretching effects range of motion (ROM), sprint, and vertical jump performances in athletes. Twenty-one healthy division III women's track and field athletes participated in the study. Subjects were tested for bilateral knee ROM; 55-m sprint time; and vertical jump height before, at 3 weeks, and after the 6-week flexibility program. Subjects were randomly assigned to treatment and control groups and warmed up with a 10-minute jog on a track before a hamstring stretching protocol. The stretching protocol consisted of four repetitions held for 45 seconds, 4 days per week. Four variables (left and right leg ROM, 55-m sprint time, vertical jump) were analyzed using a repeated-measures analysis of variance design. No significant differences (P <= 0.05) were found with any of the four variables between the stretching and control groups. Six weeks of a static hamstring stretching protocol did not improve knee ROM or sprint and vertical jump performances in women track and field athletes. The use of static stretching should be restricted to post practice or competition because of the detrimental effects reported throughout the literature. Based on the current investigation, it does not seem that chronic static stretching has a positive or negative impact on athletic performance. Thus, the efficacy of utilizing this practice is questionable and requires further investigation.